Spatial trend analysis of Hawaiian rainfall from 1920 to 2012. (18th August 2016) - Frazier, Abby G.; Giambelluca, Thomas W.
ABSTRACT: Spatial patterns of rainfall in Hawai'i are among the most diverse in the world. As the global climate warms, it is important to understand observed rainfall variations to provide context for future changes. This is especially important for isolated oceanic islands where freshwater resources are limited, and understanding the potential impacts of climate change on the supply of freshwater is critical. Utilizing a high‐resolution gridded data set of monthly and annual rainfall for Hawai'i from January 1920 to December 2012, seasonal and annual trends were calculated for every 250‐m pixel across the state and mapped to produce spatially continuous trend maps. To assess the stability of these trends, a running trend analysis was performed on 34 selected stations. From 1920 to 2012, over 90% of the state experienced drying trends, with Hawai'i Island, and in particular the western part of the island, experiencing the largest significant long‐term declines in annual and dry season rainfall. The running trend analysis highlighted the multi‐decadal variability present in these trends, and revealed that the only region in the state with persistent annual and dry season trends through the study period is the western part of Hawai'i Island; for most other regions, the drying trends were not significant until the most recent part of the record was included. These results support previous studies that indicate drying across the state over recent decades, and reveal the timing of upward and downward trends as well as important spatial details for natural resource management in Hawai'i.